评估局部用补骨脂酚和视黄醇用于缓解面部光致老化的效果. (4th February 2019) - Dhaliwal, S.; Rybak, I.; Ellis, S.R.; Notay, M.; Trivedi, M.; Burney, W.; Vaughn, A.R.; Nguyen, M.; Reiter, P.; Bosanac, S.; Yan, H.; Foolad, N.; et al.
Abstract : Linked Article:  Dhaliwal et al. Br J Dermatol 2019;180 :289–296